Recessions are bad for workplace safety - Jan Boone; Jan C. van Ours; Jean-Philippe Wuellrich; Josef Zweimüller (Institute for the Study of Labor (IZA), 2011)
Workplace accidents are an important economic phenomenon. Yet, the pro-cyclical fluctuations in workplace accidents are not well understood. They could be related to fluctuations in effort and working hours, but workplace accidents may also be affected by reporting behavior. Our paper uses unique data on workplace accidents from an Austrian matched worker-firm dataset to study in detail how economic incentives affect workplace accidents. We find that workers who reported an accident in a particular period of time are more likely to be fired later on. And, we find support for the idea that recessions influence the reporting of moderate workplace accidents: if workers think the probability of dismissals at the firm level is high, they are less likely to report a moderate workplace accident.
urn:nbn:de:101:1-201105173243
Keywords: I10; J60; J81; 330; workplace accidents; economic incentives; cyclical fluctuations